Diffusion Tensor Imaging of Patients with HIV and Normal-appearing White Matter on MR Images of the Brain - Filippi, Christopher G.; Uluǧ, Aziz M.; Ryan, Elizabeth; Ferrando, Steven J.; van Gorp, Wilfred (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: HIV enters the CNS early in the course of infection and produces neuropsychiatric impairment throughout the course of illness, which preferentially affects the subcortical white matter. The development of a neuroimaging marker of HIV may allow for the earliest detection of cognitive impairment. The purpose of this study was to determine whether MR diffusion tensor imaging can detect white matter abnormalities in patients who have tested positive for HIV.METHODS: Ten patients with HIV (eight men and two women; mean age, 42 years) underwent MR imaging of the brain with MR diffusion tensor imaging, which included routine fluid-attenuated inversion recovery and fast spin-echo T2-weighted imaging. Diffusion constants and anisotropy indices were calculated from diffusion tensor maps. Peripheral viral load, Centers for Disease Control staging, and cluster of differentiation 4 levels were determined.RESULTS: All patients had normal results of MR imaging of the brain, except for mild atrophy. Four of 10 patients had undetectable viral loads. These patients were receiving highly active antiretroviral therapy. The diffusion constant and anisotropy were normal. Four of 10 patients had viral loads between 10,000 and 200,000. Diffusion anisotropy in the splenium and genu was significantly decreased (P < .02). The diffusion constant of the subcortical white matter was elevated in the frontal and parietooccipital lobes (11%). Two of 10 patients had viral loads >400,000. Anisotropy of the splenium was half normal (P < .0004) and of the genu was decreased 25% (P < .002). The average diffusion constant was diffusely elevated in the subcortical white matter.CONCLUSION: Calculating the diffusion constant and anisotropy in the subcortical white matter and corpus callosum in patients with HIV detected abnormalities despite normal-appearing white matter on MR images and nonfocal neurologic examinations. Patients with the highest diffusion constant elevations and largest anisotropy decreases had the most advanced HIV disease. Patients with the lowest viral load levels, who had normal anisotropy and diffusion constants, were receiving highly active antiretroviral therapy.